The Influence of the Every One is A Teacher Here Type Active Learning Strategy on IPAS Learning Outcomes - Rahmi Rahmini; Vika Martahayu; Rifki Hanif Setiawan (Journal of Practice Learning and Educational Development, 2026)
The effectiveness of learning activities in the classroom greatly influences students’ academic achievement. One teaching approach considered to be highly effective is the AL-ETH strategy, which emphasizes active student participation by allowing learners to teach the subject matter to their peers. This research aims to investigate the impact of the AL-ETH method on IPAS learning outcomes of fifth-grade students at SD Negeri 08 Koba. The study applied a quantitative research design with a quasi-experimental approach. Data collection involved pretests and posttests, with instruments that had previously been validated for reliability and validity. The resulting data were then subjected to normality and homogeneity tests to verify their suitability for statistical analysis. The findings from the normality test showed that the control group had significance values of 0.233 for the pretest and 0.085 for the posttest. Similarly, the experimental group obtained significance values of 0.380 and 0.121 for the pretest and posttest, respectively. Since all values exceeded the 0.05 threshold, the data from both groups were deemed to be normally distributed. In addition, the homogeneity test revealed that both the pretest and posttest data were homogeneous, with significance values of 0.515 and 0.557. Based on these findings, the alternative hypothesis was accepted, suggesting that the “Everyone Is A Teacher Here” (AL-ETH) strategy had a statistically significant positive effect on improving IPAS learning outcomes among fifth-grade students at SD Negeri 08 Koba.